Empirical analysis on the critical success factor for benchmarking implementation in palm oil industry - Mahmud, Fatimah; Kamar, Ahmad Nazif Noor; Sorooshian, Shahryar; Dahan, Suziyana Mat; Zainuddin, Hamzah (2018)
Palm oil industry is the backbone of Malaysian commodities market that contributed to the nation economic stability. In order to sustain and stay competitive, this industry needs to continuously improve its productivity and process efficiency. Benchmarking implementation can be used to identify operational, strategic gaps and to search for best practice that would reduce the gap. However, there are few empirical research conducted using benchmarking technique and obviously, there are no studies that clearly demonstrate the benchmarking critical success factors (CSFs) specifically for palm oil industry. Hence, the main objective of this study is to investigate the CSFs for palm oil industry benchmarking implementation. In this research, mixed method design was employed, which comprise of quantitative and qualitative approach. Pilot study and reliability test were conducted on the research instrument to ensure its validity and reliability. The final survey instrument was distributed via postal mail to 350 palm oil mill managers and 350 oil palm plantation managers in Malaysia and giving a response rate of 49%. Empirical data shows respondents have high perception on the benchmarking benefits towards development of this industry and the importance of practicing the CSFs in benchmarking implementation. However, the actual practice of CSFs is still at low. On overall, there is positive correlation between the eight identified benchmarking CSFs. Later, a qualitative study was conducted to explore benchmarking implementation in this industry by investigating the question on ‘how does benchmarking give the impact to this industry performance'. Case study conducted in eight palm oil mills revealed that benchmarking implementation is still at an intermediate stage, incomplete benchmarking cycle and there is no comprehensive documentation system. Benchmarking implementation gives the benefit to the companies by enhancing company production and operation performance, improve the employee and customer satisfaction, accelerate the organizational prospects and subsequently improve the company financial management. It is hoped that the findings obtained from this research can be used as a guide for palm oil industry to obtain full benefits from the benchmarking initiative with optimal use of resources and avoid failure during implementation.